The Effect of High Temperature on Styrene Monomer Migration from Polystyrene - Mat Shayuti, Muhammad Shafiq (Universiti Teknologi Petronas, 2008)
Polystyrene (PS) cup was characterized thermally and chemically before being tested for its styrene monomer migration behavior under the influence of temperature. The. difference in thermal properties measured and the pure PS with PS cup may have been due to the additives employed during the manufacturing of the cup. Fourier transfer infrared spectroscopy (FTIR) test results showed the chemical compounds that made up the PS cup, such as aromatic compound and also substitution pattern of benzene ring. There were 2 types of stimulants employed in the study namely distilled water and cooking oil. PS cups containing the liquid stimulants were placed in an oven with temperature ranging from room temperature to 100°C with 25°C increment for each sample. Cooking oil was selected as a liquid stimulant in the study because oil simulated the fatty medium, while distilled water simulated the aqueous medium of beverages. Gas chromatography-mass spectrometry (GC-MS) detected styrene traces in the cooking oil and not in distilled water at all temperatures. In general as temperature increased, the migration of styrene from the PS cup into the cooking oil also increased. As the temperature increased, the molecules move faster due to higher kinetic energy and therefore collide more frequently. Thus, the proportion of collisions that could overcome the activation energy for the reaction increased with temperature, resulting in higher migration rate. However, at temperature above 75°C, the migration rate jumped relatively high, suggesting the possibility of the PS cup's wall damage, which could enhance and facilitate the styrene migration. In addition styrene solubility in the cooking oil may have increased significantly beyond 75°C, resulting in higher styrene migration. Arrhenius equation was used to analyze and model the relationship between temperature and the amount of styrene migration. From the experiment, the highest styrene migration resulted in styrene content in cooking oil of only 1.12 x 10·4 weight percent. This was well below the maximum allowable limit of 0.5 weight percent.